Hydrogen-assisted exhaust gas recirculation in Cascabela thevetia biodiesel-fueled diesel Engines: Towards sustainable energy solutions for clean power applications - Sakthi Murugan Veeraraghavan; Lakshmikanth G; Ganesan Subbiah; Beemkumar N; Vijay J. Upadhye; Yuvarajan Devarajan; Lakshay Bareja (Case Studies in Thermal Engineering)
This study explores the performance, emissions, and combustion characteristics of Cassia Thevitia (CT100) biodiesel, blended with exhaust gas recirculation (EGR) at 10 % and 20 % by volume, and hydrogen induction at 12 LPM, in a single-cylinder Kirloskar TV1 engine. At full load, CT100 biodiesel without EGR achieved a BTE of 31.5 %, a 0.96 % increase over diesel's 31.2 %. The introduction of EGR reduced BTE by 4.13 % and 8.89 % at 10 % and 20 % EGR, respectively, due to oxygen dilution effects. However, the Brake Specific Energy Consumption (BSEC) increased with the addition of EGR, reaching 12.815 MJ/kWh for 10 % EGR and 13.705 MJ/kWh for 20 % EGR, due to the dilution of oxygen. Emission analysis revealed that CT100 biodiesel, without EGR, led to a 14.5 % reduction in unburnt hydrocarbon (UHC) emissions and a 34.7 % reduction in carbon monoxide (CO) emissions compared to diesel. Nitrogen oxide (NOx) emissions, which initially increased by 15.4 % for CT100 biodiesel without EGR (2101 ppm vs. 1821 ppm for diesel), were effectively reduced by 4.2 % at 10 % EGR and by 19 % at 20 % EGR. Smoke opacity was reduced by 29 % (44 % vs. 62 % for diesel) without EGR and remained 17.7 % lower than diesel even with 20 % EGR, highlighting the cleaner combustion characteristics of CT100 biodiesel. These results align with the Sustainable Development Goals (SDGs), particularly SDG 7 (Affordable and Clean Energy) and SDG 13 (Climate Action), by fostering the use of cleaner energy sources and reducing greenhouse gas emissions. The findings advocate for the wider adoption of CT100 biodiesel in transportation, contributing to a sustainable energy transition and emission reduction in the sector.